Hubungan Pengalaman Kerja dengan Efikasi Diri Perawat dalam Penanganan Pasien di Instalasi Rawat Intensif RSD dr. Soebandi Jember - Nabila Syahdana R (Fakultas Keperawatan, 2026)
Introduction: Intensive Care Units require nurses to have strong clinical competence and psychological readiness in managing critically ill patients. Self-efficacy is essential in influencing nurses' performance and quality of care in high pressure settings. Based on social cognitive theory by Albert Bandura, mastery experience gained through work experience is a key source of self-efficacy development. This study aims to examine the relationship between work experience and nurses' self-efficacy in patient care at the Intensive Care Unit of Dr. Soebandi Regional Hospital, Jember. Method: This study used a quantitative descriptive correlational design with a cross-sectional approach. A total of 67 nurses were selected through total sampling from the ICU, ICCU, RICU, PICU-NICU sections of the Intensive Care Unit of Dr. Soebandi Regional Hospital, Jember. Data were collected using the Work Experience questionnaire and the General Self-Efficacy (GSE) scale, and analyzed using Spearman's rank correlation due to the non-normal distribution of the data. Result and Discussion: Of the 67 respondents, the majority (92.5%) were categorized as having high work experience, while 52.2% demonstrated a high level of self-efficacy. Statistical analysis using the Spearman Rank test revealed a significant association between work experience and nurse’s self-efficacy (p = 0.015), indicating that increased work experience was associated with higher confidence in managing critically ill patients. The Odds Ratio value of 0.297 indicated a weak association, indicating that although work experience contributes to the development of self-efficacy, it is not the sole determining factor. This finding implies that additional elements, such as sociodemographic factors, structured training, professional development opportunities, and workplace support, may also influence nurse self-efficacy in intensive care settings. Conclusion: There is a correlation between work experience and nurses' selfefficacy in handling patients in the Intensive Care Unit of Dr. Soebandi Regional General Hospital, Jember
:: Finalisasi Repositori File 4 Juni 2026_Kurnadi
Keywords: Work Experien; Efikasi Diri; Perawat; Instalasi Rawat Intensif; Patient Care